Bacterial extracellular vesicles: emerging mediators of gut-liver axis crosstalk in hepatic diseases - Zhou, Yutong; Sun, Yong; Yin, Pengsheng; Zuo, Shi; Li, Haiyang; Cao, Kun (Frontiers in Cellular and Infection Microbiology, 2025)
Bacterial Extracellular Vesicles (BEVs) are key mediators of cross-talk between gut microorganisms and host organs, playing an especially important role in the gut-liver axis. In this paper, we systematically review the mechanisms of BEV production, their classification, and their regulatory networks in liver diseases. BEVs carry pathogenic factors such as lipopolysaccharide (LPS) and bacterial DNA, which can enter the circulatory system by disrupting the intestinal barrier and target the liver to induce metabolic abnormalities, including insulin resistance. Furthermore, through activation of signaling pathways such as LPS/TLR4, cGAS/STING, and TGF-β, BEVs promote the progression of metabolism-associated fatty liver disease (MAFLD), liver fibrosis, and hepatocellular carcinoma. In addition, BEVs show dual potential in the diagnosis and treatment of liver diseases: on one hand, they can be used as non-invasive biomarkers to enhance diagnostic specificity through multi-omics analysis; on the other hand, engineered and modified BEVs, as well as probiotic BEVs (e.g., from Lactobacillus and Bifidobacterium species), can regulate lipid metabolism, reduce inflammation, and even enhance immunotherapy by targeting the tumor microenvironment. However, the heterogeneity of BEVs, efficient isolation techniques, storage stability, and clinical translation remain major challenges in current research. In the future, combining multi-omics techniques to resolve the molecular fingerprints of BEVs, optimizing isolation methods, and exploring their potential as precision medicine tools will be necessary to advance the study of the gut-liver axis toward clinical applications.